Estimating multiproduct and product‐specific scale economies for agricultural cooperatives. (28th March 2019) - Pokharel, Krishna P.; Featherstone, Allen M.
Abstract: This article estimates multiproduct and product‐specific scale economies, scope economies, and cost efficiency with single and annual cost frontiers using a nonparametric approach. Multiproduct scale and scope economies are found that suggests increasing scale and product diversification can reduce cost for agricultural cooperatives. Many agricultural cooperatives experience economies of scale indicating that variable returns to scale as opposed to constant returns to scale is the appropriate technology for modeling agricultural cooperatives. Product‐specific scale economies for all outputs are close to one indicating that individual outputs are operating close to constant returns to scale. Annual frontier estimates show that cooperatives have become less cost efficient over time, but scale and scope economies remain relatively consistent across years. Further, results show that economic measures obtained from the single frontier are statistically different from those measures calculated from annual frontiers, suggesting that the cost frontier has shifted over time. The trade‐off between cost efficiency and multiproduct scale economies indicates that smaller cooperatives can reduce a higher percentage of cost by increasing the scale of operations rather than just becoming cost efficient. Because larger incentives exist for small cooperatives to increase scale, mergers will likely continue until economies of scale are exhausted in the industry.